THE APPLICATION OF SCIENTIFIC LEARNING STRATEGY TO IMPROVE STUDENTS’ WRITING SKILLS IN LEARNING ENGLISH AT SMA MUHAMMADIYAH DISAMAKAN - Bakya, Rahmat Muhammadatul; Hj. Ilmiah; Sangkala, Ismail (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2022)
Rahmat Muhammadatul Bakya, 2023. The Application of Scientific Learning Strategy to Improve Students’ Writing Skills in Learning English at the Second Grade Students’ of SMA Muhammadiyah Disamakan. The thesis of English Education Department, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar, Guided by Hj. Ilmiah and Ismail Sangkala. The objective of the research was to find out the improvement of the students’ writing skills in learning english at the second grade in term of content, organization, and grammar. The research applied scientific strategy with one group pre test and post test design. The subject of the research was the second grade sudents’ of XI SMA Muhammadiyah Disamakan academic year 2021-2022. The sample consists of 9 students. The research was held in first until fourth meetings. Based on the data analysis showed that there was a significant difference between pretest and posttest. The research findings indicated that Scientific Learning Strategy was effective to improve the students’ writing skill in term of content, organization, and grammar. It was proved by the students’ mean score in pretest was 67.43 and posttest was 73.51. it showed that the students’ writing skill in posttest was higher than pretest. The value of t-test from content, organization, and grammar was 6.64 and it was greater than t-table 2.160 at the level of significant (p) = 0,05 and degree of freedom (df) = 9-1 = 8, it was found that the result of t-test value was greater than t-table (6.64>2, 060). It is said that the null hypotesis (H0) was rejected and the alternative hypotesis (H1) was accepted. With regard to previous results, it can be concluded that the use of scientific learning strategy in the teaching and learning process significantly can improve the students writing skill in recount text. The students made a good improvement on the aspect of content, organization and grammar.